Study The Difference Between The Planified Training Load And The Accomplished Training Load In Football During The Competition Period - Meslem , Mohamed; Bouhal , Faycel (sports creativity, 2025)
The study aims at knowing the difference between the planified load training and accomplished load training during competition period ,and that it is why we used the compared description method on a sample contains 32 players that was used by the intentional method and to collect data’s we used polar team 2 device, after having collected the data’s and statically treated it we found that difference with stastical significance exists in football for the between of the accomplished load training .